Надгробие с рельефом сюжета “загробной трапезы” и надписью из раскопок Ольвии [Pavel Diatroptov: A Gravestone Relief Depicting a Funeral Banquet From Olbia] - Диатроптов, П. Д. (Hyperboreus, 2007)
The author publishes a gravestone from Olbia with an inscription and a relief depicting a funeral banquet. In all probability the relief is a late fourth-century Athenian work, while the inscription was added in Olbia in the earlier half of the third century BC.